2021
DOI: 10.1111/gbi.12467
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for microbial ureolysis in the rapid formation of carbonate tufa mounds

Abstract: Modern carbonate tufa towers in the alkaline (~pH 9.5) Big Soda Lake (BSL), Nevada, exhibit rapid precipitation rates (exceeding 3 cm/year) and host diverse microbial communities. Geochemical indicators reveal that carbonate precipitation is, in part, promoted by the mixing of calcium‐rich groundwater and carbonate‐rich lake water, such that a microbial role for carbonate precipitation is unknown. Here, we characterize the BSL microbial communities and evaluate their potential effects on carbonate precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…Although tufa carbonate can form entirely abiotically as a result of calcium‐charged groundwater emerging into alkaline lake water (Nielsen & DePaolo, 2013) or degassing of supersaturated waters in the splash zone of streambanks, it is increasingly thought that biology plays a role in overcoming chemical kinetic inhibition of carbonate formation in each of these environments and results in rapid mineralization (Arp et al., 2010; e.g., Medina Ferrer et al., 2022; Turner & Jones, 2005). Rapid tufa carbonate mineralization has recently been linked to the enzymatic activity (e.g., urease, carbonic anhydrase) of photosynthetic cyanobacteria at other modern lakes in the Great Basin by accelerating CO 2 hydration/HCO 3 − dehydration and CO 2 degassing reactions (Medina Ferrer et al., 2022). Some dendritic tufa fabrics that have been described as “abiogenic” still require negatively charged microbial EPS to attract Ca 2+ cations and seed nucleation of calcium carbonate dendrites in the streambank splash zones, necessitating the presence of life in the depositional environment (Turner & Jones, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tufa carbonate can form entirely abiotically as a result of calcium‐charged groundwater emerging into alkaline lake water (Nielsen & DePaolo, 2013) or degassing of supersaturated waters in the splash zone of streambanks, it is increasingly thought that biology plays a role in overcoming chemical kinetic inhibition of carbonate formation in each of these environments and results in rapid mineralization (Arp et al., 2010; e.g., Medina Ferrer et al., 2022; Turner & Jones, 2005). Rapid tufa carbonate mineralization has recently been linked to the enzymatic activity (e.g., urease, carbonic anhydrase) of photosynthetic cyanobacteria at other modern lakes in the Great Basin by accelerating CO 2 hydration/HCO 3 − dehydration and CO 2 degassing reactions (Medina Ferrer et al., 2022). Some dendritic tufa fabrics that have been described as “abiogenic” still require negatively charged microbial EPS to attract Ca 2+ cations and seed nucleation of calcium carbonate dendrites in the streambank splash zones, necessitating the presence of life in the depositional environment (Turner & Jones, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The abundance and mineralogy of the chemical sediments at Searles indicate that they were hyperalkaline and thus did not require biology to induce carbonate mineralization (X. Guo & Chafetz, 2012; Ingalls, Blättler, et al., 2020; Smith, 2009). Although tufa carbonate can form entirely abiotically as a result of calcium‐charged groundwater emerging into alkaline lake water (Nielsen & DePaolo, 2013) or degassing of supersaturated waters in the splash zone of streambanks, it is increasingly thought that biology plays a role in overcoming chemical kinetic inhibition of carbonate formation in each of these environments and results in rapid mineralization (Arp et al., 2010; e.g., Medina Ferrer et al., 2022; Turner & Jones, 2005). Rapid tufa carbonate mineralization has recently been linked to the enzymatic activity (e.g., urease, carbonic anhydrase) of photosynthetic cyanobacteria at other modern lakes in the Great Basin by accelerating CO 2 hydration/HCO 3 − dehydration and CO 2 degassing reactions (Medina Ferrer et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The sites are typically enriched with a high concentration of sulfur and heavy metals that can interact with sulfur (Colovic et al, 2018; Zakari et al, 2021). Bacteria can also increase soil porosity and permeability by breaking down urea, potentially making it easier for plants to colonize abandoned mines (Medina Ferrer et al, 2022). The FUNGuild analysis found that the fungi in IC1 and IC2 groups displayed distinctive dung saprotroph, and the dung‐inhabiting fungi play an essential ecological role in decomposing and recycling nutrients from animal dung (Sarrocco, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been a strong bias towards the study of metabolic genes involved, for instance, in energy‐generating oxidation–reduction processes such as sulphur‐oxidation (Dahl, 2020 ), iron‐oxidation (Kappler et al, 2021 ) or coding for chemistry‐altering enzymes such as ureases (e.g. Ferrer et al, 2021 ) or phosphatases (e.g. Skouri‐Panet et al, 2018 ).…”
Section: What Is the ‘Mineral Phenotype’ And What Controls It?mentioning
confidence: 99%